Microbial contamination of Indian currency notes in circulation - NV, Pradeep; Anupama; BS, Marulasiddaiah; M, Chetana; P, Gayathri; SN, Maduri (Journal of Research in Biology, 2012)
Paper currency, an exchangeable fomite, is constantly subjected to contamination. The objective of this study was to identify the micro-organisms present on the currency notes circulating in India. A total of 12 currency notes (Rs.10, Rs.50 and Rs.500) were randomly collected from bank, Municipal Corporation, food sellers, butchers, hospital. Persons handling the notes were asked to deposit them in sterile envelopes. The notes were taken to the laboratory immediately and microorganisms were identified using standardized microbiological techniques. All the notes collected during this study were contaminated by micro-organisms. Species isolated were Escherichia coli, klebsiella pneumonia, Pseudomonas aeruginosa and Staphylococcus aureus. The currencies used by public (bank, hospital, Municipal Corporation) in India were found to be extremely contaminated with various pathogenic bacteria followed by the currency used by butchers and food sellers. Infected currency was identified as a potential public health hazard, as pathogens could spread by circulating the contaminated notes. We recommend that currency notes must be handled with caution.